Two middle kingdom stelae of nn-RN=F and SNBJ in the Egyptian museum Cairo (CGC 20524-20521) - Ibrahim ABD EL SATTAR (Fayoum University, 2019)
The aim of this paper is to publish and study two Abydos stelae preserved now in the magazine of the Middle Kingdom in the Egyptian Museum in Cairo under the numbers (CGC 20524 and 20521), with discussion of the meaning of their names and titles. Furthermore, it aims to transcribe, translate, and comment on their epigraphical features. The first stela belongs to a person named Nn-rn⸗f and his brother ©wj. While the second is a stela of ¤nbj son of Ibj. The artistic style, the orthographic and paleographic features suggest a dating to the beginning of the Twelfth Dynasty for the stela of Nn-rn⸗f (the reign of Senowsret I), while the style and the epigraphical features of the stela of ¤nbj are typical of the Late Twelfth Dynasty or the Early Thirteenth Dynasty.